The Level of Implementation of Expanded Program of Immunization - Jonathan Hamonangan Tobing (Jurnal Skolastik Keperawatan, 2025)
Background: This study examined gaps in routine childhood immunization by assessing the level of Expanded Program on Immunization (EPI) implementation in two purposively selected community health centers in West Bandung. Method: Secondary data from immunization registers (medical records) were collected, producing a sample of 334 records. A descriptive quantitative design was used with frequency/percentage summaries and an independent-samples t-test for between-center comparison. Results: show that Community Health Center (CHC) A had partial implementation for several antigens and boosters (for example lower Hepatitis B and measles-booster coverage), whereas Community Health Center (CHC) B achieved predominantly moderate implementation levels (notably higher HB and measles coverage and booster uptake). The difference in overall implementation between centers was statistically significant (t = 24.87, p < 0.001). Conclusions: implementation quality varies markedly between CHCs and lower caregiver education and later booster rollout likely explain poorer performance in CHC A. Recommendation to prioritize targeted caregiver education, active follow-up/home visits for missed children, and strengthened monitoring and booster program rollout to improve EPI completeness and reduce vaccine-preventable disease risk.